2022
DOI: 10.1101/2022.02.06.22270457
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protection of COVID-19 vaccination and previous infection against Omicron BA.1, BA.2 and Delta SARS-CoV-2 infections

Abstract: Given the emergence of the SARS-CoV-2 Omicron BA.1 variant and the roll-out of booster COVID-19 vaccination, evidence is needed on protection conferred by primary vaccination, booster vaccination and previous SARS-CoV-2 infection against Omicron BA.1 compared with Delta infection. We employed a test-negative design and used multinomial logistic regression on data from community PCR testing in the Netherlands, from 22 November 2021 to 19 January 2022. S-gene target failure (SGTF) was used as proxy for Omicron B… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
42
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 18 publications
(32 reference statements)
11
42
1
Order By: Relevance
“…17,[22][23][24][25][26][27] Elsewhere during the Omicron period, two manuscripts from Qatar instead suggest higher protection conferred by prior infection vs. two-dose vaccination against symptomatic Omicron re-infection; 28,29 whereas, preprint from the Netherlands reports lower protection from prior infection (25%;95%CI:21-29) vs. two-dose vaccination (33%;95%CI:31-35). 30 Additional studies may be needed to clarify these comparisons, recognizing the challenge in standardizing based upon the time since last event (infection or vaccination).…”
Section: Discussionmentioning
confidence: 99%
“…17,[22][23][24][25][26][27] Elsewhere during the Omicron period, two manuscripts from Qatar instead suggest higher protection conferred by prior infection vs. two-dose vaccination against symptomatic Omicron re-infection; 28,29 whereas, preprint from the Netherlands reports lower protection from prior infection (25%;95%CI:21-29) vs. two-dose vaccination (33%;95%CI:31-35). 30 Additional studies may be needed to clarify these comparisons, recognizing the challenge in standardizing based upon the time since last event (infection or vaccination).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis estimated efficacy/effectiveness drops ∼10% for severe disease and ∼20% for infection over five months 85 . These drops appear to be more extreme for the Omicron variant; but evidence suggests “booster” doses - administered in many countries during Fall/Winter 2021 - enhance immunogenicity and effectivenes 20,26,27,29,136,182,183 . However, the WHO stresses prioritization of primary doses globally 184 .…”
Section: Discussionmentioning
confidence: 99%
“… Study, year and Reference Country and study design Effectiveness Tseng et al, 2022 [ 77 ] USA Test-negative case-control study including 26,683 SARS-CoV-2 cases Effectiveness of booster vaccination 71.6% (after 14–60 days), 47.4% (>60 days) Monge et al, 2022 [ 78 ] Spain Case-control study among 3,111,159 individuals receiving a booster vaccine and equal number of matched controls Booster effectiveness (after 7–34 days): mRNA-1273 booster: 52.5% (95% CI: 51.3–53.7) BNT162b2 booster: 46.2% (95% CI: 43.5–48.7) Abu-Raddad et al, 2022 [ 79 ] Qatar Retrospective cohort study including 230.526 receivers of a BNT162b2 booster vaccination Booster effectiveness: mRNA-1273 booster (after 35 days): 50.8% (95% CI: 43.4–57.3) BNT162b2 booster (after 49 days): 50.1% (95% CI: 47.3–52.8%) Accorsi E et al, 2022 [ 80 ] USA Test-negative case-control analysis among 70,155 tests from 4,666 sites Effectiveness 66.3% (95% CI: 64.3–68.1) against Omicron after BNT162b2 or mRNA-1273 booster Thomson et al, 2022 [ 81 ] USA Test-negative case-control analysis among 222722 emergency department and urgent care Encounters Effectiveness 94% (95% CI: 93–94) against Delta and 82% (95% CI: 79–84) against Omicron after BNT162b2 or mRNA-1273 booster Kislaya I et al, 2022 [ 61 ] Portugal Case-control study of 4,898 omicron variant cases among 13,134 SARS-CoV-2 infections Booster effectiveness against omicron variant 68.8% (95% CI: 46.4–81.7%), against delta 94.0% (95% CI: 93.4–94.6) Odds ratio for omicron breakthrough infection after booster: 5.2 (95% CI: 3.1–8.8) vs. delta UK Health Security Agency [ 82 ] United Kingdom UK Health Security Agency COVID-19 vaccine surveillance report Effectiveness against mild infection 2–4 weeks after mRNA booster 60–75%, after >15 weeks 25–40% Effectiveness against hospitalization initially ∼90%, dropping to ∼75% after 10–14 weeks for BNT162b2 booster 90–95% up to 9 weeks after mRNA-1273 booster. Andeweg SP et al, 2022 [ 49 ] the Nether...…”
Section: What Are the Causes Of Breakthrough Infections?mentioning
confidence: 99%
“…The Omicron variant, characterized by great immune evasion, escapes the majority of existing SARS-CoV-2 neutralizing antibodies [ 46 ]. However, recent data have shown that a third-dose mRNA vaccine booster, or double vaccination followed by Delta breakthrough infection, or prior infection followed by mRNA vaccine double vaccination, all appear to restore neutralizing activity against Omicron [ [47] , [48] , [49] ].…”
Section: What Are the Causes Of Breakthrough Infections?mentioning
confidence: 99%